LEARNING STYLES RELATIONSHIP TO VALUE GPA CHEMISTRY EDUCATION STUDENTS MULAWARMAN - Abdul Majid (PROSIDING SEMINAR KIMIA, 2015)
The student's learning style is typical of the way a person in performing activities of learning, where learning style is one factor that can affect student cumulative grade point. Therefore, research on